2020
DOI: 10.1016/j.biortech.2020.123168
|View full text |Cite
|
Sign up to set email alerts
|

Hygienization and microbial metabolic adaptation during anaerobic co-digestion of swine manure and corn stover

Abstract: This thesis is an investigation of the use of anaerobic co-digestion (AcoD) of swine manure (SM) and corn stover (CS) to produce biogas and reduce the environmental health risk of manure.Laboratory-scale mesophilic (38 °C) batch AcoD of different ratios of SM and CS were conducted to measure cumulative methane potential, organic matter reduction, hygienization efficiency, and microbial metabolic adaptation in response to increasing total solids (TS). The results revealed the highest methane potential and great… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 106 publications
(202 reference statements)
2
3
0
Order By: Relevance
“…Thus, the accumulation of VFAs which is attributable to high total solids, could have contributed to the inability of the resident E. coli to regain viability, as well as rapid coliform elimination [ 25 , 33 ]. This observation also agrees with the work of Arias et al [ 26 ] who reported more pathogen killing with higher total solids during batch AD. Although Fagbohungbe et al [ 27 ] reported an increase in E. coli and coliform inactivation only with an increase in ISR during batch AD of human faecal material, in this study, it was observed that ISR < 0.5 or ≥2, which led to high acidity or alkalinity, respectively, during the initial days of digestion would enhance E. coli and coliform inactivation during mesophilic AD.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Thus, the accumulation of VFAs which is attributable to high total solids, could have contributed to the inability of the resident E. coli to regain viability, as well as rapid coliform elimination [ 25 , 33 ]. This observation also agrees with the work of Arias et al [ 26 ] who reported more pathogen killing with higher total solids during batch AD. Although Fagbohungbe et al [ 27 ] reported an increase in E. coli and coliform inactivation only with an increase in ISR during batch AD of human faecal material, in this study, it was observed that ISR < 0.5 or ≥2, which led to high acidity or alkalinity, respectively, during the initial days of digestion would enhance E. coli and coliform inactivation during mesophilic AD.…”
Section: Discussionsupporting
confidence: 93%
“…Enterococci are very resistant to environmental stress and treatment [ 11 , 37 ]. The findings from this study agrees with the work of Arias et al [ 26 ], who observed no clear trend in Enterococcus inactivation after 75 d of batch mesophilic AD, as well as Do et al [ 38 ], who also reported the resistance of Enterococcus during a 90 d batch AD of pig slurry.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…A consortium of Clostridium , Bacteroides , Ruminococcus and Methanosarcina applied on particulated rice straw gave a maximum yield of 275 mol of hydrogen per g of substrate [ 167 ]. Members of anaerobic Clostridiales class were also able to produce methane from wheat straw, swine manure and corn stover [ 168 , 169 ].…”
Section: Bacterial Biorefinerymentioning
confidence: 99%
“…Corn stover refers to the residual biomass left in the field after harvesting grain, including leaves, stalks, husks, tassels and cobs. While maize grain is utilized as a substrate for ethanol production ( Schwietzke et al, 2009 ) and maize silage is used as a substrate for biogas production in Europe and North America ( Veluchamy et al, 2019 ), corn stover is currently under-utilized as a substrate for renewable energy production ( Arias et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%